Poverty and health (OECD ParisFR, 2003)
Expands and deepens the DAC guidelines on poverty reduction, which were endorsed by OECD Ministers of Development Co-operation and heads of development agencies at the 2001 DAC High Level Meeting. Provides directions on the most effective ways of supporting a pro-poor health in partner countries.
Bibliography: p. 91-92